Clinical research of arteriovenous fistula as an initial vascular access - Shi You-shan; Chen Tian-hao; Huang Zheng (Linchuang shenzangbing zazhi)
ObjectiveTo explore the clinical characteristics and application value of arteriovenous fistula （AVF） as an initial vascular access to provide references for improving its use rate.MethodsFrom February 2016 to December 2020， retrospective analysis was performed for 170 patients with maintenance hemodialysis （MHD）. There were 114 males and 56 females with an average age of （61.68±14.79）（20-92） years. According to the difference of vascular access for initial dialysis， they were divided into two groups of AVF and central venous catheter （CVC）. Demographic profiles， clinical data， laboratory examinations， major risk events and mortality within 1 year of two groups were compared.ResultsIn AVF group （n=51）， there were 33 males and 18 females with an average age of （61.71±12.05） years； In CVC group （n=119）， there were 81 males and 38 females with an average age of （61.67±15.87） years. No significant inter-group differences existed in composition ratio of gender， age or primary disease （P>0.05）. Using rate of AVF for initial vascular access was 30.00%. AVF group had higher education and better economic status and the difference was statistically significant （P<0.05）. The follow-up period of 27（12-72） months was longer than that of control group （P<0.05）. Serum albumin（37.87±0.72）g/L and eGFR（7.11±2.53）mL·min-1·（1.73m2）-1 were higher in AVF group than those in control group （P<0.05）. Systolic blood pressure （144.33±16.20） mmHg was better than those of control group and the difference was statistically significant （P<0.05）. Multivariate analysis suggested that eGFR （OR=0.620， P=0.031）， serum albumin （OR=0.790， P=0.003） and systolic blood pressure （OR=1.030， P=0.001） were independent factors in selecting AVF as an initial vascular access. Within 1 year of dialysis， no death occurred in AVF group and 12 deaths in control group. The difference was statistically significant （P<0.05）. The occurrence of major risk events such as cardiovascular and cerebrovascular events， lung infections and vascular access infections was lower than that in control group （P<0.05）.ConclusionSelecting vascular access is correlated with eGFR， serum albumin and systolic blood pressure at this center. And choosing AVF as an initial vascular pathway plays some role in reducing the occurrence of major risk events and death.